2015
DOI: 10.1016/j.toxlet.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Affinities of organophosphate flame retardants to tumor suppressor gene p53: An integrated in vitro and in silico study

Abstract: The binding affinities of OPFRs for p53 DNA fragment were studied. The interaction of 9 OPFRs with p53 was explored by UV and fluorescence spectroscopy. The electrostatic potentials were found to be the dominant interactions. The QSAR had good robustness, predictive ability and mechanism interpretability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, as described in Section 1 , two OPEs concerned in this study can cause damage to the liver of organisms. Therefore, it is important to evaluate the risk of OPEs to the human liver using hepatocellular toxicity data [ 18 ]. In vitro data on human hepatocellular toxicity from the EPA used in our study makes our health risk assessment more robust than previous risk assessments based on animal data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as described in Section 1 , two OPEs concerned in this study can cause damage to the liver of organisms. Therefore, it is important to evaluate the risk of OPEs to the human liver using hepatocellular toxicity data [ 18 ]. In vitro data on human hepatocellular toxicity from the EPA used in our study makes our health risk assessment more robust than previous risk assessments based on animal data.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that high doses of TDCPP can promote an increase of liver weight in rats [ 17 ]. TPHP significantly increased the expression of p53 gene in human embryonic liver L02 cells, thereby affecting cell apoptosis [ 18 ]. Reported health effects in humans include sick building syndrome from Tri-n-butyl phosphate (TnBP) [ 19 ], contact dermatitis, reduction of sperm counts and inhibition of androgen receptors from TPHP, and reduced thyroid hormone levels from TDCPP [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under in vitro conditions, the human alveolar (A549) cells, hepatocellular (HepG2) cells, and colon (Caco‐2) cells exposed to TCPP have been attributed to induce toxicity at high concentration (200 μM) (An et al, 2016). Similarly, human liver cells (L02) exposed to TCPP demonstrated their cytotoxic effects at high concentrations (100 and 1000 μM) (Li, Wang, et al, 2017) and effectively bind to the promoter region of p53 gene (Li et al, 2015). Recently, TCPP (300 μM) exposure for 48 h significantly affected the survival of A549 cells and initiated oxidative stress, mitochondrial dysfunction, and apoptotic cell death (Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative structure-activity relationship (QSAR) has been widely used to interpret and predict the toxicity mechanism of compounds (Harju et al, 2009;Li et al, 2013). Previous studies showed that QSARs could characterize the structure features affecting the binding affinity of chemicals to sex hormone binding globulin (SHBG) (Liu et al, 2016(Liu et al, , 2017, affecting the octanol-air partition coefficient (K OA ) of OPFRs (Wang et al, 2017b), and affecting the binding constants of OPFRs interacting with tumor suppressor genes (p53) (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%